Design And Simulation Of Cmos Based Low Voltage Bandgap Reference Circuitry - Tan , Chin Ling (2016)

(untitled)
The objective of this thesis is to study the performance of the BGR circuit by using Metal Oxide Semiconductor (MOS) transistor to replace the Bipolar Junction Transistor (BJT) circuit. As known bipolar transistor is better characterize over temperature. However, bipolar transistor required a high threshold voltage to operate as compared to MOS transistor; Therefore, the bipolar transistor has replaced by MOS transistor to improve performance of BGR for low voltage application lower than 1.2V and to reduce fabrication process. The result of the Op-Amp has shown it able to achieve 74.34dB gain as well as 62.16 degree of phase margin, which stable for integration with BGR circuit. After that, the Op-Amp circuit is then incorporate into the design of for a complete BGR architecture. The proposed design of BGR circuit able to achieve similar performance, which produce the maximum low voltage about 446.05mV and the minimum of 440.2mV at a temperature range of -10℃ to 100 ℃. Besides, the reference voltage generated is stable after the supply voltage higher than 1.2V, which meant the circuit are still able to provide accurate and stable reference voltage for a variety of supply voltage changes. Furthermore, the circuit has high PSRR values at -70.59 dB, to ensure enough headroom for noise rejection from the supply voltage. However, the circuit has a higher temperature coefficient which is 118.12 ppm /℃ . Lastly, the design completed with post-layout simulation and the area of BGR circuit including dummy are being consume of 133μm x 140μm of die area.